Prefrontal cortex activation and working memory performance in individuals with non-clinical depression: Insights from fNIRS - Seungju Lim; Ji-Hyuk Park (Acta Psychologica)
Previous research has extensively explored cognitive and neural deficits in clinically diagnosed depression, but the early stages of depression, where symptoms do not meet clinical thresholds, are less explored. This study investigated neurocognitive markers in individuals with non-clinical depression. The study assessed working memory (WM) performance and hemodynamic responses of prefrontal cortex (PFC) in 30 individuals with non-clinical depression and 41 healthy controls using two-back tasks with four stimulus types: numbers, letters, shapes, and emotional facial expressions. Hemodynamic responses were measured via oxyhemoglobin (HbO) using functional near-infrared spectroscopy. Results showed that individuals with non-clinical depression have significantly lower WM performance compare to healthy controls, particularly for shape- and emotional facial expression-based tasks. No differences were observed for the number- and letter- based tasks. Additionally, individual with non-clinical depression exhibited elevated HbO levels, indicating increased PFC activation. Specifically, significant HbO differences observed in the bilateral ventrolateral PFC during shape-based tasks, and in the left medial, bilateral orbital, and bilateral ventrolateral PFCs during emotional facial expression-based tasks. In conclusion, individuals with non-clinical depression may experience WM deficits and PFC dysregulation, even without a clinical diagnosis. This study highlights the role of stimulus type in understanding WM performance and PFC activation in depression.